Features in the formation of the structural state of low-carbon micro-alloyed steels after eletron beam welding - Laukhin, Dmytro; Poznyakov, Valerii; Kostin, Valery; Beketov, Olexander; Rott Nataliіa; Slupska, Yuliia; Dadiverina, Lilia; Liubymova-Zinchenko, Olga (Eastern-European Journal of Enterprise Technologies, 2021)
Welding thermomechanically-strengthened materials is accompanied with certain difficulties in terms of loss of strength characteristics in the zone of thermal influence. This issue can be resolved by using the technological welding schemes that include fusion of materials in a narrow contact area. One such technological scheme is electron beam welding, which is currently widely used to fabricate structures from refractory and chemically active materials. One of the main advantages of the electron beam welding process is a small quantity of heat input, which leads to the formation of narrow zones of melting and thermal influence and, as a result, minor deformities in the structure of the material. The welded joint can structurally be divided into several zones, which differ in the morphological characteristics of the structure. The most interesting, in terms of ensuring the quality of the joint, are the boundaries between the zones. It has been shown that the use of local heating sources, which is the case at electron beam welding, leads to the migration of the boundaries of grains. As a result, clear intersections, fusion lines, form at the boundaries between zones of the welded joint. The formation of the structural state of a welded joint is predetermined by the simultaneous course of several processes. First, a crystallization from the liquid state – the formation of a welded joint structure, as well as the boundary between a welded joint and the zone of thermal influence. Second, the phase-structural transformations in the solid state – a thermal impact zone, the boundary between a thermal impact zone and the main metal. Given this, one should note that the geometry and quality of joints at electron beam welding are more interrelated than in other welding techniques. Thus, one of the main parameters that ensure the quality of a welded joint is the structural state of the material that forms during welding